2016
DOI: 10.1002/btm2.10032
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of light‐induced liposome permeabilization

Abstract: Liposomes have been widely studied for drug delivery applications. The inclusion of photoactive molecules into liposomes opens the possibility of light-controlled cargo release to enhance drug biodistribution or bioavailability at target sites. Membrane permeabilization induced by light can be an effective strategy for enhancing cargo delivery with spatial and temporal control, which holds potential for chemophototherapy approaches. Several diverse mechanisms have been reported including light-induced oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 85 publications
0
63
0
Order By: Relevance
“…The most commonly used phospholipids for liposome formation include lecithins from egg and soy, as well as sphingomyelins [38]. Common variations to the phospholipid hydrophobic acyl (fatty acid) tail include the degree of saturation (i.e., saturated vs. unsaturated) and length, which can impact the oxidizing properties and drug release profiles of liposomes [39]. For example, Luo et al showed that photodynamic therapy-mediated oxidation of unsaturated lipids (i.e., 1,2-dioleoyl-sn-glycero-3-phosphocholine, or DOPC, 18:1 PC) in the liposomal bilayer could facilitate the controlled release of doxorubicin.…”
Section: Toxicological Evaluation Of Liposomes and Their Building Blocksmentioning
confidence: 99%
“…The most commonly used phospholipids for liposome formation include lecithins from egg and soy, as well as sphingomyelins [38]. Common variations to the phospholipid hydrophobic acyl (fatty acid) tail include the degree of saturation (i.e., saturated vs. unsaturated) and length, which can impact the oxidizing properties and drug release profiles of liposomes [39]. For example, Luo et al showed that photodynamic therapy-mediated oxidation of unsaturated lipids (i.e., 1,2-dioleoyl-sn-glycero-3-phosphocholine, or DOPC, 18:1 PC) in the liposomal bilayer could facilitate the controlled release of doxorubicin.…”
Section: Toxicological Evaluation Of Liposomes and Their Building Blocksmentioning
confidence: 99%
“…Cationic and unsaturated 1,2‐dioleoyl‐3‐trimethylammonium‐propane (DOTAP, 8 mol%) was introduced to the lipid composition to provide a neutral‐to‐positive zeta potential of +10–12 mV to balance toxicity, circulation and tumor accumulation as described previously . The incorporation of unsaturated lipids such as DOTAP could also accelerate light‐triggered drug release via liposomal lipid oxidation as shown by others . In our study, photosensitizers (BPD or PpIX) were adsorbed in the liposomal lipid bilayer via hydrophobic and ionic interactions, resulting in an entrapment efficiency of 76.4 ± 1.2% and 44.9 ± 0.7% for Nal‐BPD and Nal‐PpIX, respectively (Table ) .…”
Section: Resultsmentioning
confidence: 84%
“…In this section, the addition of photosensitizers rather than the use of two-photon absorption or upconverting nanoparticles is highlighted. However, it is important to note that these strategies have been previously used in phototriggerable liposomes [24][25][26], and recent reviews of phototriggerable liposomes are available [27][28][29].…”
Section: Liposomesmentioning
confidence: 99%